Development of “Hydro Pure Pro (HPP)” Water Filter Technology to Reduce Iron (Fe) and TDS Levels in Drilled Well Water - Husnul Hatimah; Dahlia Rosma Indah; Nurwahidah; Muhammad Fauzi Zulkarnaen (Postgraduate, University of Mataram, 2026)
High levels of iron (Fe) and total dissolved solids (TDS) in well water remain a major groundwater quality problem in Indonesia. This study aimed to develop and evaluate the effectiveness of a Hydro Pure Pro (HPP) water filtration system based on a multi-stage aeration–filtration process to reduce Fe and TDS concentrations. The HPP system combines activated carbon, zeolite, silica sand, mountain sand, and a reverse osmosis (RO) unit as final treatment, with a focus on assessing the effects of activated carbon raw materials (coconut shell and wood) and carbon bed thickness on adsorption performance. The results showed that coconut shell activated carbon exhibited superior performance, reducing Fe from 0.606 mg/L to 0.135 mg/L (77.72%) and TDS from 540 mg/L to 390 mg/L (27.8%) at a thickness of 20 cm. Increasing the carbon thickness to 30 cm improved removal efficiency to 79.9% for Fe and 28.7% for TDS, after which performance tended to stabilize. This improvement is attributed to the higher specific surface area and well-developed microporous structure of coconut shell activated carbon, which enhances Fe²⁺ adsorption through ion exchange and surface functional group interactions. In conclusion, the HPP system demonstrates high effectiveness and economic feasibility, making it a promising filtration technology for improving the quality of borehole water in community settings.